Decentralization without democracy - Kosec, Katrina; Mogues, Tewodaj (Trustees of Princeton University, 2020)
Increasingly, decentralization is being adopted by countries in which assumptions made by formal models of decentralization, such as electoral accountability and population mobility, fail to hold. How does decentralization affect public service delivery in such contexts? The authors exploit the partial rollout of decentralization in the autocratic context of Ethiopia and use a spatial regression discontinuity design to identify its effects. Decentralization improves delivery of productive services, specifically, agricultural services, but has no effect on social services, specifically, drinking water services. This finding is consistent with a model in which local leaders have superior information about the public investments that will deliver the greatest returns and they are incentivized by decentralization to maximize citizens’ production—on which rents depend—rather than citizens’ utility. These findings shed light on nonelectoral mechanisms through which decentralization affects public goods provision and help to explain decentralization’s mixed effects in many nondemocratic settings.